2009
DOI: 10.1007/s11255-009-9576-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in hemodialysis patients: hepatitis C virus infection makes sense

Abstract: HCV infection impairs QOL, especially in mental aspects, in hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 34 publications
7
15
0
Order By: Relevance
“…In agreement with our study, Afsar et al [4] found positive correlation between haemoglobin levels and the following SF-36 subscales: physical functioning, role-physical limitation, bodily pain, general health perception, vitality, social functioning, role emotional and mental health subscales, PCS and MCS.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In agreement with our study, Afsar et al [4] found positive correlation between haemoglobin levels and the following SF-36 subscales: physical functioning, role-physical limitation, bodily pain, general health perception, vitality, social functioning, role emotional and mental health subscales, PCS and MCS.…”
Section: Discussionsupporting
confidence: 93%
“…In this group QOL was not affected by age, but affected by gender and males were found to have higher scores in role emotional, bodily pains and PCS compared to females. Afsar et al [4] demonstrated that the majority of the SF-36 subscales were lower in anti-HCV antibody positive HD patients compared with in anti-HCV antibody negative patients, with an independent association between anti-HCV antibody positivity and MCS of SF-36, but not with PCS, which was in agreement with our study.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations